2023
DOI: 10.3390/biomedicines11020378
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Elevated Homocysteine and Metabolic Syndrome in a Community-Dwelling Middle-Aged and Elderly Population in Taiwan

Abstract: (1) Background: Metabolic syndrome has become a serious health problem in society. Homocysteine is a biomarker for cardiovascular disease. We investigated the relationship between homocysteine levels and metabolic syndrome. (2) Methods: A total of 398 middle-aged and elderly individuals were included in our study. First, we divided the participants into two groups: the metabolic syndrome group and the nonmetabolic syndrome group. Second, according to tertiles of homocysteine levels from low to high, the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…A meta-analysis has shown that both active and passive smoking can negatively impact HDL [ 4 ]. This is due to several factors, including higher homocysteine levels in smokers, which hurts HDL [ 29 ]. Additionally, smoking may reduce estrogen levels, leading to a decrease in HDL [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has shown that both active and passive smoking can negatively impact HDL [ 4 ]. This is due to several factors, including higher homocysteine levels in smokers, which hurts HDL [ 29 ]. Additionally, smoking may reduce estrogen levels, leading to a decrease in HDL [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine emerges as a promising biomarker for cardiovascular disease, potentially pivotal in linking metabolic syndrome with cardiovascular conditions. Elevated homocysteine levels are thought to inflict damage upon endothelial cells [ 4 ]. A recent investigation found that increased levels of insulin can disrupt the processing of homocysteine, resulting in higher concentrations of this compound.…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation found that increased levels of insulin can disrupt the processing of homocysteine, resulting in higher concentrations of this compound. In metabolic syndrome, insulin resistance manifests as elevated insulin levels [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study is expected to contribute significantly to the disease management and prevention of middle-aged and elderly adults receiving primary health care. Several publications have already been published based on this database, and this paper is no exception [22][23][24][25][26][27]. This study aimed to investigate differences in the relationship of vitamin D levels with sitting time between middle-aged and older adult populations in Taiwan.…”
Section: Introductionmentioning
confidence: 99%